Faktor - Faktor Mempengaruhi Kepatuhan Wajib Pajak dalam Membayar Pajak Bumi dan Bangunan di DKI Jakarta - Parapat, Diana Madeline (Jurnal Akuntansi, 2023)
The purpose of this research is to analyze the effect of taxpayer attitudes, taxpayer awareness, and tax knowledge on taxpayer compliance in paying land and building taxes in DKI Jakarta. From a sample of 104 respondents, the authors conclude: (1) Taxpayer attitudes have a positive effect on taxpayer compliance in paying PBB. (2) Taxpayer awareness has no significant effect on taxpayer compliance in paying PBB. (3) Knowledge of Taxation has a positive and significant effect on taxpayer compliance in paying PBB. This study used the Quantitative Method and data analysis tool IBM SPSS Statistics 26 for data analysis.   Keywords: Land and Building Tax, Taxpayer Attitude, Taxpayer Awareness, Tax Knowledge.